Sleep Disorders in Rodent Models of Parkinson’s Disease - Medeiros, Daniel de Castro; Lopes Aguiar, Cleiton; Moraes, Márcio Flávio Dutra; Fisone, Gilberto (Frontiers in Pharmacology, 2019)
Sleep disorders are frequently diagnosed in Parkinson’s disease and manifested in the prodromal and advanced stages of the disease. These conditions, which in some cases affect more than 50% of PD patients, include hypersomnia, often manifested as excessive daytime sleepiness, insomnia, characterized by delayed initiation and fragmentation of sleep at night, and disruption of rapid eye movement (REM) sleep, resulting in loss of atonia and dream enactment. Standard dopamine replacement therapies for the treatment of motor symptoms are generally inadequate to combat sleep abnormalities, which seriously affect the quality of life of PD patients. Rodent models still represent a major tool for the study of many aspects of PD. They have been primarily designed to eliminate midbrain dopamine neurons and elicit motor impairment, which are the traditional pathological features of PD. However, rodent models are increasingly employed to investigate non-motor symptoms, which are often caused by degenerative process affecting multiple monoaminergic and peptidergic structures. This review describes how neurotoxic and genetic manipulations of rats and mice have been utilized to reproduce some of the major sleep disturbances associated with PD and to what extent these abnormalities can be linked to non-dopaminergic dysfunction, affecting for instance noradrenaline, serotonin and orexin transmission. Strengths and limitations are discussed, as well as the consistency of results obtained so far, and the need for models that better reproduce the multisystemic neurodegenerative nature of PD, thereby allowing to replicate the complex etiology of sleep-related disorders.